ASURANSI MIKRO UNTUK MODA TRANSPORTASI OJEK OJEK - Rukaesih A. Maolani; Acmad Sudiyar Dalimunthe (Institut Transportasi dan Logistik Trisakti, 2018)
This study aimed at finding out “Ojek’s” drivers’ knowledge about micro insurance and their interest in becoming the customers. The study used 60 “Ojek’s” drivers as respondents. It was conducted in several areas of Jakarta and Bekasi from October 2017 to January 2018.. The data were collected through questionnaires and analyzed using descriptive statistics. The conclusion obtained is most of “Ojek’s” drivers in the study sites already knew about micro insurance but only few of them who are interested in becoming the insurance customers.